Reverse innovation in health care : - Govindarajan, Vijay (Harvard Business Review Press, 2018)
Health care in the United States and other nations is on a collision course with patient needs and economic reality. For more than a decade, leading thinkers including Michael Porter and Clayton Christensen have argued passionately for value-based health care reform: replacing delivery based on volume and fee-for-service with competition based on value, as measured by patient outcomes per dollar spent. Though still a pipe dream here in the United States, this kind of value-based competition is already a reality--in India. Facing a giant population of poor, underserved people and a severe shortage of skills and capacity, some risk-taking private enterprises have found a way to deliver high-quality health care, at ultra-low prices, to all patients who need it. Govindarajan and Ramamurti studied these Indian value-based models in depth. After investigating forty health care organizations and conducting field research on sixteen, they identified seven "exemplar" providers that consistently delivered high-quality health care at ultra-low cost, while being profitable, financially sustainable, and able to scale up their operations. Their secret sauce consists of five principles that work together to produce value-based care. Arguing that now is the time for the United States and other "rich" nations to learn from the "poor," this book shows how the innovations developed by these Indian exemplars are already being practiced by some far-sighted US providers--reversing the typical flow of innovation in the world. The authors describe four different pathways being used by these organizations to apply Indian-style principles to attack the exorbitant costs, uneven quality, and incomplete access to health care in the United States.